Discourse analysis in adults with and without communication disorders : a resource for clinicians and researchers - Coelho, Carl A.; Cherney, Leora Reiff; Shadden, Barbara B. (Barbara Bennett) (Plural Publishing, Inc., 2023)
"Discourse Analysis in Adults With and Without Communication Disorders: A Resource for Clinicians and Researchers provides state-of-the-art information about discourse analysis with sections on Aging, Aphasia, Cognitive Communication Disorders, and Neurodegenerative Diseases. Section are introduced and organized by expert clinical researchers, and contain"--